Assessment of prevalence and risk factors of pre-eclampsia and eclampsia in tertiary care hospital - Tandur, Anoop N.; Kuriakose, Ashni; Laldinpuia, Samuel K.; G. R., Nataraj; K., Lokeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pre-eclampsia and eclampsia are two conditions in which high blood pressure essentially complicates pregnancy by causing oedema and/or albuminuria. The present study was undertaken among pregnant women to determine the prevalence of pre-eclampsia and eclampsia as well as to assess the association between risk factors and pre-eclampsia, risk factors and eclampsia and to determine the complications of pre-eclampsia and eclampsia. Method: A prospective observational study was conducted over a period of six months at obstetrics inpatient department of Basaveshwara Medical college and hospital, Chitradurga. Results: Total of 583 pregnant women who visited the inpatient department were enrolled, out of which study showed that the prevalence of pre-eclampsia was 91 (15.67%) and eclampsia was 54 (9.26%). A statistically varied significance level of p=0.00001 to 0.05 for risk factors such as age, primigravida, birth interval, pre-existing disease, placental abnormalities, multiple pregnancy, past history, proteinuria were found to be associated with pre-eclampsia and eclampsia. The complications such as pre-term birth, neonatal death HELLP syndrome (hemolysis, elevated liver enzymes, and low platelets), Foetal growth restriction were found. Out of which pre-term birth was the most observed complication in both pre-eclampsia and eclampsia. Conclusions: Considering the significant association between the risk factors and pre-eclampsia, eclampsia from the study we conclude that early diagnosis is essential. Lack of antenatal care, limited access to medical facility and lack of resources have influenced in late diagnosis in our set up. As evidenced by study proper awareness should be provided to the pregnant women.